Clinical advances in EGFR-TKI combination therapy for EGFR-mutated NSCLC: a narrative review - Zhang, Qianru; Wang, Ruo; Xu, Lu (Translational cancer research, 2023)
Mutations located in epidermal growth factor receptor (EGFR) tyrosine kinase domains have been described as the 'Achilles heel' of non-small cell lung cancer (NSCLC) and can be targeted by epidermal growth factor receptor-tyrosine kinase inhibitors (EGFR-TKIs). However, the clinical benefits of EGFR-TKIs are limited, and drug resistance inevitably occurs in NSCLC patients after long-term exposure to certain drugs. EGFR-TKI combination therapies, including combined targeted therapy, radiotherapy, chemotherapy, and immunotherapy, have shown promise in addressing this issue. This literature review analyzed the rationale and controversies of clinical research related to various EGFR-TKI combination therapies. The PubMed database was searched to retrieve articles published from January 1, 2001 to April 15, 2023 using the following Medical Subject Headings (MeSH) terms: "EGFR-mutated non-small cell lung cancer" and "clinical trial". Google Scholar was also reviewed to retrieve additional articles. The search was limited to articles published in English. In this review, we summarized EGFR-TKI combination therapies, including combined targeted therapy, radiotherapy, chemotherapy, and immunotherapy, most of which have shown efficacy and safety in patients with EGFR-mutated NSCLC. A number of clinical studies with large sample sizes have analyzed the activity and toxicity of combined therapies and explored potential and well-tolerated treatment options. EGFR mutations have been detected in many NSCLC patients and can be targeted by EGFR-TKIs. However, drug resistance after long-term exposure remains a significant challenge for this type of treatment. Most clinical trials have shown that the combination of EGFR-TKIs and targeted therapy, chemotherapy, radiotherapy or immunotherapy is efficacious and safe in the treatment of EGFR-mutated NSCLC. It should be noted that in some instances, serious adverse events have led to the termination of trials. However, EGFR-TKI combination therapy is indeed an effective approach for the treatment of patients with EGFR-mutated NSCLC and deserves further development.